High school students' motivation to participate in extracurricular futsal training during the Covid-19 pandemic - Razali; Muhammad Iqbal (Inspiree)
The  purpose  of  the study. The purpose of this study was to determine the motivation of the Futsal extracurricular participants at Senior High School.